Digital Legal Literacy Counseling to Prevent Juvenile Delinquency in the Social Media Era - Sulistyaningsih, Puji; Nabila, Jihan Arsya; Rahayu, Mayla Dwi; Araya, Alingga Passa Dhanes Dina; Erlangga, Rasty Rachelia (Universitas Muhammadiyah Magelang, 2025)
In today's digital era, adolescents often fall into delinquency, such as spreading negative content on social media, cyberbullying, and data privacy violations due to low digital legal literacy. This problem is exacerbated by a lack of understanding of the Electronic Information and Transactions Law (UU ITE), the Personal Data Protection Law, and the Criminal Code (KUHP) regarding juvenile crime. This community service activity aims to promote digital legal literacy to prevent juvenile delinquency through interactive and engaging legal counseling. The strategies implemented include digital-based educational approaches, such as online and face-to-face workshops with analysis of actual legal cases, role-playing simulations, and the creation of educational content on Instagram and TikTok. The problem-solving method is carried out through preparation (identifying the risk of delinquency), implementation (counseling to high school/vocational school students), and evaluation (pre-post tests and questionnaires). The findings show a significant increase in understanding of digital legal literacy, a reduction in the intention to engage in digital delinquency, and the ability of participants to create independent educational content. The conclusion of this activity is that the integration of digital legal literacy with familiar social media has proven effective in preventing juvenile delinquency and is worthy of widespread replication.